Pengaruh Sudut Kontak Statis terhadap Penyebaran Droplet di Atas Permukaan Padat yang Dipanaskan pada Bilangan Weber Menengah - M. Dyan Susila (JURNAL MECHANICAL, 2010)
The influence of static contact angle on the spreading of droplet on a heated solid surface has been studied experimentally. Static contact angle was important parameter which influenced the impact behavior and heat transfer during the interaction of droplet and solid surface. Droplet substance was destilated water with initial diameter of 2.5 mm and solid surface material was stainless steel. Impact energy was expressed in Weber number, they were 52.1 and 57.7. Solid surface temperature was varied from 60−285°C to cover the heat transfer regimes, they were single-phase liquid, nucleate boiling, transition boiling, and film boiling. Static contact angle were 0°, 35.04°, and 85.72°.           As result, it was known that static contact angle has influence on spread characteristic after droplet impacting solid surface. Spreading factor increases due to the decrease of static contact angle. Evaporation time decreases due to the decrease of static contact angle.Keywords: droplet, impact, spreading, static contact angle